Unveiling the dynamic future of Ethiopian lakes: A call for conservation - Abera, Wuletawu; Getaneh, Yonas (CGIAR, 2024)
NEXUS Gains research reveals ecological trends for lakes in Ethiopia, and provides essential insights for prioritizing lake conservation strategies